Optimization of Case Reflection Discussion Implementation as Continuous Professional Development for Nurses - Khoyrunnisa, Ulfa; Novieastari, Enie; Yatnikasari, Aat (Indonesian Journal of Global Health Research, 2024)
X Hospital Jakarta is a hospital that has implemented Case Reflection Discussion as a program for the continuing professional development for nurses. However, its implementation has not been optimal. A change is needed to enhance the optimization of the Case reflection Discussion by using Graham Gibb’s reflective cycle approach. Pilot Project method. It begins with problem identification, problem analysis, prioritization of issue, development a plan of action, implementation, and evaluation. There was a 70% increase in nurses who achieved a good level after the socialization. The evaluation of skill levels from each team showed that each team had an excellent skill level. The implementation of Case Reflection using Graham Gibb’s reflection cycle appoach has the potential to greatly benefit for nursing professional development. X hospital should distribute and socialize guidelines for the implementation of continuing professional development for nurses and Standard Operating Procedure for Case Reflection Discussion using Graham Gibb’s reflective cycle approach to all care units.